The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4062/biomolther.2013.043
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of the Seed of Zizyphus jujuba var. spinosa Ameliorates Cognitive Impairment Induced by Cholinergic Blockade in Mice

Abstract: In the present study, we investigated the effect of ethanolic extract of the seed of Zizyphus jujuba var. spinosa (EEZS) on cholinergic blockade-induced memory impairment in mice. Male ICR mice were treated with EEZS. The behavioral tests were conducted using the passive avoidance, the Y-maze, and the Morris water maze tasks. EEZS (100 or 200 mg/kg, p.o.) significantly ameliorated the scopolamine-induced cognitive impairment in our present behavioral tasks without changes of locomotor activity. The amelioratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
5
23
0
1
Order By: Relevance
“…[16][17][18][19][20] Further, numerous brain pathology models have indicated memory-enhancing effects of EZJ. 21,22) These findings demonstrated that EZJ can modulate brain function and may show anti-AD actions. To clear this hypothesis, we examined the action of EZJ on Aβ-induced LTP impairment.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…[16][17][18][19][20] Further, numerous brain pathology models have indicated memory-enhancing effects of EZJ. 21,22) These findings demonstrated that EZJ can modulate brain function and may show anti-AD actions. To clear this hypothesis, we examined the action of EZJ on Aβ-induced LTP impairment.…”
mentioning
confidence: 77%
“…Extraction was conducted two times with 50% ethanol under reflux (80-85°C) for 3 h. Evaporation was conducted under reduced pressure and the extract was dried using spray dryer (yield, 13.8%). 21) EZJ was standardized with spinosin (molecular weight (MW), 608.55, >0.5%). And the chemical profile of EZJ is presented in supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was conducted as described elsewhere. 13) Proteins were transferred onto a polyvinylidene difluoride (PVDF) membrane in trans- fer buffer and further separated at 100 V for 2 h at 4°C. The membrane was incubated for 2 h with blocking solution (5% skim milk) at 4°C, followed by overnight incubation with a primary antibody (pERK, anti-rabbit, 1 : 3000; pGSK-3β, antirabbit, 1 : 3000; ERK, anti-rabbit, 1 : 3000; GSK-3β, anti-goat, 1 : 3000).…”
Section: )mentioning
confidence: 99%
“…The acquisition and retention trials of the passive avoidance task were conducted for 2 days, as previously described elsewhere (Lee et al ., ). All tests were performed in a box consisting of two identical chambers (20 × 20 × 20 cm) divided by a guillotine door (5 × 5 cm) between the two chambers.…”
Section: Methodsmentioning
confidence: 97%